KAJIAN SISTEM PENANGANAN MATERIAL SISTEM PRODUKSI SECARA MANUAL DAN BERBASIS AUTOMATED GUIDED VEHICLE (AGV) (Studi Kasus di Divisi Spinning PT Primissima (Persero)) - , HASNA KHAIRUNNISA ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Along with the development of manufacturing industry and business, the needs of faster service time to the consumer in fulfilling their demand makes the material handling system as one of important manufacturing infrastructure. The textile industry in Indonesia has a huge role to the national economy. So the textile industry need to maintain the balance between productivity to fulfill the consumer demand with the production cost spent. This research is done in one of textile industry in Spinning Division of PT. Primissima (Persero). The material handling in this division is done manually by a transporter. The company policy to apply a dedicated manual material handling system, the load that the transporter have to bear when pushing, and the late delivery of material from spinning to winding station makes the study of Spinning Division material handling system needs to be done. This research is done by build a simulation model of the real system of Spinning Division using Pro Model Software. The simulation model verification and validation is done by then. The simulation model of the real system is then used to do the optimization on the material handling system with Automated Guided Vehicle. Ten scenarios are developed based on handling capacity of AGV. Based on those scenarios, the 6th scenario is the best scenario with the handling capacity of 1500 cones, where it has 500-750 cones more than the real system. This AGV system will eliminate the transporter workload, so the company can eliminate the labor cost for transporter then replace it with AGV investment. The economic analysis is also build to study the feasibility of the AGV investment. Based on this research, the replacement of manual material handling system using transporter to automatic material handling system using AGV is proved to increase the production productivity. The AGV system can increase the final yarn output of winding machine of 6,096% or 905 cones per day. The feasibility analysis result shows that the new material handling investment using AGV is feasible to run, with the Net Present Value (NPV) of IDR 136.819.215,68, Internal Rate of Return (IRR) of 14%, and Pay Back Period (PBP) in 4,19 years. The replacement analysis shows that the AGV system will reduce the total cost to IDR 20.240,00 per day or IDR 7.286.320,00 per year.